Bauran Eceran Dalam Meningkatkan Partisipasi Anggota : Studi Pada Koperasi Produsen Tempe Tahu Indonesia Kota Bandung - Fuji Irfani, Rizki; Gunadi, Trida (Koaliansi : Cooperative Journal, 2021)
The object of this research is the "Kopti" Soybean Trade. Soybean Trading Unit's income fluctuated, indicating the low participation of members in the "Kopti" Soybean Trading Unit. The retail mix is ​​one of the advantages that can be created by cooperatives, namely focusing its business on customer satisfaction where customers will be loyal to consume or use cooperative services continuously. This study uses descriptive methods and scoring techniques with a Likert scale. The results showed that members' responses regarding the implementation of the retail mix at the Soybean Trading Unit "Kopti" were quite good, but there were some indicators that were still not good, such as selling prices compared to competitors, sales promotions, product availability, product variants, interiors and lighting. For this reason, the Soybean Trading Unit "Kopti" must pay attention to the retail mix expected by members, so that the participation of members as buyers can increase. Suggestions from this study are to evaluate and improve the retail mix that has been implemented but is still not optimal or running well, such as advertising, sales promotions, price comparisons with competitors, lighting or outside appearance of the store so that members are more interested in transacting at the Soybean Trading Unit. “Kopti” and provide direct economic benefits to members.